Anatomical and Physiological Features of the Child’s Body - Muxamattairovna, Baxavadinova Zamira; Djuraevna, Saxibova Mavlyuda (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the basics of the anatomical, physiological and physical development of the adolescent generations organism, the lifestyle characteristics of adolescents.